The Paulicians: heresy, persecution, and warfare on the Byzantine frontier, c.750-880 - Dixon, Carl (The medieval mediterranean, 2022)
In a searching challenge to the paradigm of medieval Christian dualism, this study reenvisions the Paulicians as largely conventional Christians engendered by complex socio-religious forces in the borderlands of Armenia and Asia Minor.